Strategies that regulate LSD1 for novel therapeutics - Meng Li; Mengge Dai; Bing Cheng; Shaotong Li; Enhui Guo; Junwei Fu; Ting Ma; Bin Yu (Elsevier, 2024)
Histone methylation plays crucial roles in regulating chromatin structure and gene transcription in epigenetic modifications. Lysine-specific demethylase 1 (LSD1), the first identified histone demethylase, is universally overexpressed in various diseases. LSD1 dysregulation is closely associated with cancer, viral infections, and neurodegenerative diseases, etc., making it a promising therapeutic target. Several LSD1 inhibitors and two small-molecule degraders (UM171 and BEA-17) have entered the clinical stage. LSD1 can remove methyl groups from histone 3 at lysine 4 or lysine 9 (H3K4 or H3K9), resulting in either transcription repression or activation. While the roles of LSD1 in transcriptional regulation are well-established, studies have revealed that LSD1 can also be dynamically regulated by other factors. For example, the expression or activity of LSD1 can be regulated by many proteins that form transcriptional corepressor complexes with LSD1. Moreover, some post-transcriptional modifications and cellular metabolites can also regulate LSD1 expression or its demethylase activity. Therefore, in this review, we will systematically summarize how proteins involved in the transcriptional corepressor complex, various post-translational modifications, and metabolites act as regulatory factors for LSD1 activity.